America's war on same-sex couples and their families : and how the courts rescued them / Daniel R. Pinello. - Pinello, Daniel R. (Cambridge University Press, 2017)
America's War on Same-Sex Couples and Their Families is a legal, political, and social history of constitutional amendments in twenty American states (with 43 percent of the nation's population) that prohibited government recognition of all forms of relationship rights (marriage, civil unions, and domestic partnerships) for same-sex couples. Based on 175 interviews with gay and lesbian pairs in Georgia, Michigan, North Carolina, Ohio, Texas, and Wisconsin, the volume has great human-interest value and chronicles how same-sex couples and their children coped within harsh legal environments. The work ends with a lively explanation of how the federal judiciary rescued these families from their own governments. In addition, the book provides a model of the grassroots circumstances under which harassed minority groups migrate out of oppressive state regimes, together with an estimate of the economic and other costs (to the refugees and their governments) of the flight from persecution.